Using information technology : - Williams, Brian K. (McGraw-Hill Companies, 2011)
Utilizing a practical, applied approach to technology, this text intends to foresee and define the impact of digital convergence, the fusion of computers and communications. It acknowledges the various priorities imposed by the Internet and World Wide Web